Evaluating the onset conditions of a thermoacoustic Stirling engine loaded with an audio loudspeaker - Hsu, Shu-Han; Lai, Chuan-Heng (Frontiers in Thermal Engineering, 2023)
This paper studies the onset conditions of a thermoacoustic Stirling engine loaded with a commercially available audio loudspeaker. The thermoacoustic engine converts supplied heat power into mechanical power in the form of sound, without any mechanical moving parts. The simplicity of the acoustical heat engine holds great promise for high reliability and low cost. By utilizing a readily available electromagnetic device, the engine can serve as a durable solution for practical applications. In this study, we assembled a commercially available moving-coil loudspeaker as a low-cost linear alternator for the thermoacoustic Stirling engine, enabling electric generation from supplied heat. We modeled the loudspeaker using linear control equations and experimentally calibrated its acoustic impedances to estimate the acoustic load. For the part of the thermoacoustic engine, we estimated its acoustic characteristics within the framework of the linear thermoacoustic theory. By solving the characteristic equation resulting from the the engine loaded with the audio speaker, we estimated the operational point of self-sustained oscillations excited by the coupling of the loudspeaker and the thermoacoustic engine system. To validate the estimations, we tested a prototype of the combined system, consisting the loudspeaker and the thermoacoustic engine. Results highlight the necessity of precise calibration and accounting for complex geometries within the acoustic load for accurate theoretical estimations, especially when incorporating a commercially available loudspeaker into a thermoacoustic engine.